Duality gives rise to Chaplygin cosmologies with a big rip - Chimento, Luis Pascual (2006)
We consider modifications to the Friedmann equation motivated by recent proposals along these lines pursuing an explanation to the observed late time acceleration. Here we show that these approaches can be framed within a theory with modified gravity, and we discuss the construction of the duals of the cosmologies generated within that framework. We then investigate the modifications required to generate extended, generalized and modified Chaplygin cosmologies, and then show that their duals belong to a larger family of cosmologies we call enlarged Chaplygin cosmologies. Finally, by letting the parameters of these models take values not earlier considered in the literature we show that some representatives of that family of cosmologies display sudden future singularities. This fact indicates that the behaviour of these spacetimes is rather different from that of generalized or modified Chaplygin gas cosmologies. This reinforces the idea that modifications of gravity can be responsible for unexpected evolutionary features in the universe. © 2006 IOP Publishing Ltd.